Dosimetric assessment of TomoDirect radiotherapy and TomoHelical radiotherapy in the clinical implementation of total skin irradiation - Wang, Haiyang; Pi, Yifei; Liu, Chunbo; Wang, Panfeng; Long, Chengzhang; Qi, Yaping; Kong, Fanyang; Han, Bin; Wang, Fangna; Jia, Fei; Liu, Lele; Xu, Dandan; et al. (Frontiers in Oncology, 2025)
PurposeThis study aims to compare the technical characteristics of TomoDirect (TD) radiotherapy and TomoHelical (HT) radiotherapy in total skin irradiation (TSI) applications. We conducted a comprehensive evaluation of dosimetric parameters and delivery efficiency in TD-based treatment planning to establish clinical guidelines for modality selection in mycosis fungoides.Materials and methodsThis retrospective study analyzed eight mycosis fungoides patients treated with TSI between June 2020 and June 2023, utilizing a 5-mm-thick diving suit bolus to enhance the skin dose distribution with a prescription of 24 Gy delivered in 20 fractions (five fractions/week). Thermoplastic masks (3 mm in thickness) were used for head/neck and thorax/abdomen region immobilization, while the lower limbs were immobilized in a vacuum cushion. Comparative treatment planning employed both TD and HT techniques, with TD plans utilizing 7, 9, and 11 equally spaced coplanar beams (0°starting angle). Ring0, Ring1, Ring2, Ring3, and Ring4, which were 1-cm thick away from the planning target volume (PTV) at distances of 0, 1, 2, 3, and 4 cm, and other normal tissues (NT) were generated. The auxiliary structures were completely blocked during planning. The other plan parameters remained consistent. Plan quality assessment compared the target mean dose (PTVmean), homogeneity index (HI), conformity index (CI), and organ-at-risk (OAR) doses between techniques, with additional evaluation of treatment delivery efficiency through time comparisons.ResultsWhen using NT, Ring4, and Ring3 auxiliary structures in complete-block mode, TD plans with more than nine beams demonstrate comparable PTVmean, HI, and CI-to-HT plans, whereas TD plans of less than nine beams exhibit inferior target coverage. Neither HT nor TD plans meet the clinical requirements when Ring2, Ring1, or Ring0 structures are fully blocked. Regarding OAR sparing, nine-beam TD and HT plans show equivalent maximum doses to optical structures (lenses, optic nerves, and chiasm) and mean doses to other OARs (oral cavity, salivary glands, lungs, heart, liver, and kidneys) with NT/Ring4/Ring3 blocking. However, both techniques fail to satisfy the OAR constraints when Ring2/Ring1/Ring0 are blocked. Treatment delivery times remain similar between modalities with NT/Ring4/Ring3 blocking, but the efficiency significantly decreases for both when deeper structures (Ring2/Ring1/Ring0) are included in the blocking protocol.ConclusionWhen employing complete-block mode for NT, Ring4, and Ring3 structures, TD plans utilizing more than nine beams demonstrate comparable dosimetric performance to HT plans in terms of target coverage, OAR sparing, and treatment delivery efficiency. However, both modalities fail to meet the clinical dosimetric requirements when deeper-seated structures (Ring2/Ring1/Ring0) are included in the blocking protocol.